HIV treatment eligibility expansion and timely antiretroviral treatment initiation following enrollment in HIV care: A metaregression analysis of programmatic data from 22 countries. - Olga Tymejczyk; Ellen Brazier; Constantin Yiannoutsos; Kara Wools-Kaloustian; Keri Althoff; Brenda Crabtree-Ramírez; Kinh Van Nguyen; Elizabeth Zaniewski; Francois Dabis; Jean d'Amour Sinayobye; Nanina Anderegg; Nathan Ford; et al. (PLoS Medicine)
Background The effect of antiretroviral treatment (ART) eligibility expansions on patient outcomes, including rates of timely ART initiation among those enrolling in care, has not been assessed on a large scale. In addition, it is not known whether ART eligibility expansions may lead to "crowding out" of sicker patients. Methods and findings We examined changes in timely ART initiation (within 6 months) at the original site of HIV care enrollment after ART eligibility expansions among 284,740 adult ART-naïve patients at 171 International Epidemiology Databases to Evaluate AIDS (IeDEA) network sites in 22 countries where national policies expanding ART eligibility were introduced between 2007 and 2015. Half of the sites included in this analysis were from Southern Africa, one-third were from East Africa, and the remainder were from the Asia-Pacific, Central Africa, North America, and South and Central America regions. The median age of patients enrolling in care at contributing sites was 33.5 years, and the median percentage of female patients at these clinics was 62.5%. We assessed the 6-month cumulative incidence of timely ART initiation (CI-ART) before and after major expansions of ART eligibility (i.e., expansion to treat persons with CD4 ≤ 350 cells/μL [145 sites in 22 countries] and CD4 ≤ 500 cells/μL [152 sites in 15 countries]). Random effects metaregression models were used to estimate absolute changes in CI-ART at each site before and after guideline expansion. The crude pooled estimate of change in CI-ART was 4.3 percentage points (95% confidence interval [CI] 2.6 to 6.1) after ART eligibility expansion to CD4 ≤ 350, from a baseline median CI-ART of 53%; and 15.9 percentage points (pp) (95% CI 14.3 to 17.4) after ART eligibility expansion to CD4 ≤ 500, from a baseline median CI-ART of 57%. The largest increases in CI-ART were observed among those newly eligible for treatment (18.2 pp after expansion to CD4 ≤ 350 and 47.4 pp after expansion to CD4 ≤ 500), with no change or small increases among those eligible under prior guidelines (CD4 ≤ 350: -0.6 pp, 95% CI -2.0 to 0.7 pp; CD4 ≤ 500: 4.9 pp, 95% CI 3.3 to 6.5 pp). For ART eligibility expansion to CD4 ≤ 500, changes in CI-ART were largest among younger patients (16-24 years: 21.5 pp, 95% CI 18.9 to 24.2 pp). Key limitations include the lack of a counterfactual and difficulty accounting for secular outcome trends, due to universal exposure to guideline changes in each country. Conclusions These findings underscore the potential of ART eligibility expansion to improve the timeliness of ART initiation globally, particularly for young adults.